Legal Protection of Students' Reproductive Health Rights through Campus Health Service Governance - Tyan Ferdiana Hikmah; Ratih Kartika Dewi; Merissa Pramudita (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2026)
Reproductive health services play an essential role in supporting students’ well-being and safeguarding their reproductive health rights. As young adults, university students face various reproductive health challenges that require accessible, confidential, and non-discriminatory services. However, the governance and implementation of reproductive health services in higher education institutions remain limited due to inadequate institutional policies, restricted access, and concerns regarding confidentiality and social stigma. This study aimed to assess the governance of reproductive health services and examine the protection of students’ rights in accessing reproductive health care. A sequential explanatory mixed-methods design was employed. Quantitative data were collected from 150 students selected through proportional stratified random sampling using a structured questionnaire, while qualitative data were obtained through in-depth interviews, focus group discussions, and document reviews involving students, campus health personnel, and university administrators. Quantitative data were analyzed using descriptive statistics, whereas qualitative findings were examined through thematic analysis. The findings revealed that although most students recognized the importance of reproductive health services, service utilization remained relatively low. The main barriers included limited awareness of available services, concerns about confidentiality, perceived social stigma, and the absence of comprehensive institutional policies. Existing campus health services primarily focused on general health care and had not adequately integrated reproductive health programs into routine service delivery. The qualitative findings further emphasized the need for stronger governance, clearer service protocols, and greater institutional commitment to protecting students’ reproductive health rights. In conclusion, strengthening institutional policies, improving service accessibility, ensuring confidentiality, and integrating reproductive health programs into campus health governance are essential to enhance the protection of students’ reproductive health rights and increase the utilization of reproductive health services in higher education institutions. Pelayanan kesehatan reproduksi merupakan komponen penting dalam mendukung kesejahteraan mahasiswa sekaligus melindungi hak-hak kesehatan reproduksi mereka. Sebagai kelompok usia dewasa muda, mahasiswa menghadapi berbagai permasalahan kesehatan reproduksi yang memerlukan layanan yang mudah diakses, menjaga kerahasiaan, dan bebas dari diskriminasi. Namun, tata kelola pelayanan kesehatan reproduksi di perguruan tinggi masih belum optimal karena keterbatasan kebijakan institusi, akses layanan yang belum memadai, serta adanya kekhawatiran terhadap kerahasiaan dan stigma sosial. Penelitian ini bertujuan untuk menganalisis tata kelola pelayanan kesehatan reproduksi serta perlindungan hak mahasiswa dalam mengakses layanan kesehatan reproduksi. Penelitian menggunakan desain sequential explanatory mixed methods. Data kuantitatif dikumpulkan dari 150 mahasiswa yang dipilih melalui teknik proportional stratified random sampling menggunakan kuesioner terstruktur. Data kualitatif diperoleh melalui wawancara mendalam, diskusi kelompok terarah, dan telaah dokumen yang melibatkan mahasiswa, tenaga kesehatan kampus, serta pengelola perguruan tinggi. Data kuantitatif dianalisis secara deskriptif, sedangkan data kualitatif dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa meskipun sebagian besar mahasiswa menyadari pentingnya pelayanan kesehatan reproduksi, tingkat pemanfaatan layanan masih rendah. Hambatan utama meliputi rendahnya pengetahuan mengenai ketersediaan layanan, kekhawatiran terhadap kerahasiaan, adanya stigma sosial, serta belum tersedianya kebijakan institusi yang komprehensif. Layanan kesehatan kampus masih berfokus pada pelayanan kesehatan umum dan belum mengintegrasikan program kesehatan reproduksi secara menyeluruh. Temuan kualitatif juga mengungkapkan perlunya penguatan tata kelola, penyusunan prosedur layanan yang lebih jelas, serta peningkatan komitmen institusi dalam melindungi hak kesehatan reproduksi mahasiswa. Dengan demikian, penguatan kebijakan institusi, peningkatan aksesibilitas layanan, jaminan kerahasiaan, serta integrasi program kesehatan reproduksi ke dalam tata kelola layanan kesehatan kampus menjadi langkah penting untuk meningkatkan perlindungan hak kesehatan reproduksi dan pemanfaatan layanan oleh mahasiswa.